2019
DOI: 10.21522/tijph.2013.07.02.art019
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Tuberculosis and the Impact of the Introduction of Genexpert on the Diagnosis of Tuberculosis in Presumptive cases of a Hospital in Nigeria

Abstract: Objective: To investigate the risk factors and impact of the introduction of XPERT MTB/RIF test on the diagnosis of pulmonary tuberculosis (TB) in presumptive cases in a General Hospital in Nigeria.Design and setting: A retrospective study that examines the record of the hospital, from January, 2015 to December, 2017. A logistic regression analysis was utilized to identify the associated factors.Results: There were total of 753 TB cases out of a total of 3639 people investigated. The rate of TB was 0.207. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The results showed that pulmonary TB mostly affects productive age (36.02 ± 12,587 years) and most of them are male (75%) (Table 1). This result is similar to the results of a previous study in Nigeria which had a mean age of 35.68 ± 14.05 years and 68.1 of them were male (Kolapo & Famuyiwa, 2018). In both of these studies, the partisipants used is someone who comes to health services to get treatment for TB.…”
Section: Resultssupporting
confidence: 89%
“…The results showed that pulmonary TB mostly affects productive age (36.02 ± 12,587 years) and most of them are male (75%) (Table 1). This result is similar to the results of a previous study in Nigeria which had a mean age of 35.68 ± 14.05 years and 68.1 of them were male (Kolapo & Famuyiwa, 2018). In both of these studies, the partisipants used is someone who comes to health services to get treatment for TB.…”
Section: Resultssupporting
confidence: 89%